factorise

Asked by  | 26th Apr, 2008, 05:00: PM

Expert Answer:

The given polynomial is 2y3 + y2 – 2y -1
y = 1 is a root of this polynomial.
Then dividing the polynomial by y – 1, we get the quotient as 2y2 + 3y + 1.
Now we solve this quadratic polynomial by splitting its middle term.
2y2 + 3y + 1 = 2y2 + 2y + y + 1
                   = 2y ( y + 1) + ( y+ 1)
                  = (y + 1) (2y + 1)
So, the factors of the given polynomial 2y3 + y2 – 2y -1 are = (y – 1) (y + 1) (2y + 1)

Answered by  | 10th May, 2008, 12:42: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.